Keabsahan Perubahan Status Hukum Desa Werwawan Menjadi Dusun Werwawan Di Kabupaten Maluku Barat Daya - Daniel Palpialy; Salmon Eliazer Marthen Nirahua; Yohanes Pattinasarany (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2022)
The transfer of the village government center from Werwawan Village to Letoda Hamlet without going through a legal product, namely a Regional Regulation. This research is a normative juridical research, and then examines and knows the answers to this problem through a concept approach, statutory approach and case approach, then from the results of the description conclusions and suggestions can be drawn. The results showed that the formation of Letoda Hamlet to become an autonomous village and the transition of legal status from Werwawan Village to a hamlet were not in accordance with the substance and legal procedures in force, including the discretion of the Deputy Regent of West Southeast Maluku to the Head of Letoda Village to move the government administration center from Werwawan Village to Letoda Hamlet which was then accompanied by Letoda Hamlet to become an autonomous village and Werwawan Village to become a hamlet which did not have legal validity and had no binding legal force and the transition of legal status from Werwawan Village to Werwawan Hamlet had no legal status. Legal amendments in the concept of administrative law, material/factual actions and legal actions taken by the Deputy Regent of West Southeast Maluku which have implications for Letoda Hamlet becoming an autonomous village and Werwawan Village becoming a hamlet in principle are government actions that are not based on law so that there are legal consequences of the government's actions so that legal actions can give rise to legal consequences administratively and therefore Letoda Hamlet which has become an autonomous village and Werwawan Village which has become a hamlet does not have legal validity so it can be annulled.